Sensitive detection and evaluation of ultrafine dust particles with a resonant terahertz metasurface [Invited] - Lee, Geon; Roh, Yeeun; Rho, Eui Young; Ryu, Yong-Sang; Seo, Minah (Optical Society of America, 2023)
We demonstrate efficient and highly sensitive detection methods for ultrafine dust and introduce a controllable evaluation way. Using the nanogaps of terahertz resonant metasurfaces where the terahertz field is greatly enhanced by the squeezed mode volume, the ultrafine dust particles were efficiently detected. The measured signal changes of the resonance can be modified in their spectral shape by the deposited particle concentrations with their effectively changed optical properties. Various resonant metasurfaces were compared and evaluated in terms of their geometrical design, relative gap size to the particle size, and particle concentration. Positioning ultrafine particles into the small nano gaps via the Polydimethylsiloxane film sweeping technique results in further significant changes in measured terahertz optical signal. The proposed method for ultrafine dust detection by photonic metasurface is promising as it guides advanced stages of ultrasensitive terahertz molecule sensors even at the real-world environmentally hazardous particulates both in qualitative and quantitative manners.& COPY; 2023 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement